Genome-wide analysis of histone H3 lysine9 trimethylation by ChIP-seq in peripheral blood mononuclear cells of uremia patients - Sui, Weiguo; He, Huiyan; Yan, Qiang; Chen, Jiejing; Zhang, Ruohan; Dai, Yong (Hemodialysis international, 2013)
Treatment of uremia is now dominated by dialysis, in some cases, patients are treated with dialysis for decades, but overall outcomes are disappointing. A number of studies have confirmed the relevance of several experimental insights to the pathogenesis of uremia, but the specific biomarkers of uremia have not been fully elucidated. Studies of the epigenome have attracted little interest in nephrology, especially in uremia. However, to date, our knowledge about the alterations in histone methylation in uremia is unclear. H3K9me3 variations were analyzed in peripheral blood mononuclear cells from 10 uremia patients and 10 healthy subjects, using chromatin immunoprecipitation followed by high‐throughput sequencing (ChIP‐seq). There were 96 genes with significantly different expressions in the uremia patients compared with the normal controls. Forty‐two increased and 54 decreased H3K9me3 genes displaying significant differences were found in uremia patients compared with healthy subjects. Five positive genes, ras‐related C3 botulinum toxin substrate 3 (RAC3), polycomb group ring finger 2 (PCGF2), myosin heavy chain 3 (MYH3), noggin (NOG), serpin peptidase inhibitor 8 (SERPINB8), were selected and quantified. Our studies indicate that there are significant alterations of H3K9me3 in uremia patients; these significant H3K9me3 candidates may help to explain the immunological disturbance and high cardiovascular complications in uremia patients. Such novel findings show the significance of H3K9me3 as a potential biomarker or promising target for epigenetic‐based uremia therapies.